(3GdeSJaGO ef eHgeGJ GdeJf hGdGSfGOs - (3CMeO Hf YHO GdQMje Hf GdMSjf GdcQOj GdYQGbj, CHh RQYI, hdj GdOjf , GHf GdYQGbj, J (B826 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CaVd Hg hHYO aEf ef GdeYdhe GdhGVM Cf CLd GdYdhe HYO Yde cJGH Gddg GdefRd Yde SfI fHjg GdeQSd s
(3BNQgG (B:s
(3hCHh HcQ CMeO Hf Ydi Hf KGHJ GdNWjH PcQ ehGdjOge hhaGJge JQcJ PcQ Pdc EP djS ef GdeHgeGJ ai TF s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs